2006
DOI: 10.1001/jama.295.10.1127
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Air Pollution and Hospital Admission for Cardiovascular and Respiratory Diseases

Abstract: Short-term exposure to PM2.5 increases the risk for hospital admission for cardiovascular and respiratory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

58
1,407
11
26

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 2,279 publications
(1,555 citation statements)
references
References 42 publications
58
1,407
11
26
Order By: Relevance
“…*Published emission factors but not reported in text. **Emission factors reported explicitly in text ᴬ Age groups according to health outcomes; ᴯ Such as ≥18 years or ≥30 years; C Environmental Benefits Mapping and Analysis Program using the concentration response function from chronic bronchitis [63], acute bronchitis [64], all-cause mortality [65,104], COPD hospitalization (Moolgavgkar 2000a, 2003) [66], asthma emergency room visits [67], work loss days [68], asthma (symptoms) [69], minor-restricted activity days [70], acute MI [71], respiratory disease [72], lower respiratory symptoms [73], and cough among asthmatic children [74]; D Probable, but not specified explicitly in the text; ᴱ Health And Air Pollution Study in New Zealand to estimate the morbidity and mortality health costs associated with traffic emissions [82]; F CVD admission >64 years: [75]; ᴳ Mortality: <75 and >75 years, respiratory disease (65 years) [76], and lung cancer [104] Morbidity: CVD, respiratory disease [76], and lung cancer [104]; H Method of transport emission estimation is quite vague in determination of emission factors; I External cost of energy to estimate the automotive pollution impact on health in Europe [81]; J Cerebrovascular disease and lower respiratory tract infection [77], preterm weight [78], low term weight [79], and CVD (Mustafic 2012) [80]; K Value of a Life Year: calculation of monetary benefits of mortality reduction using a life tables approach. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…*Published emission factors but not reported in text. **Emission factors reported explicitly in text ᴬ Age groups according to health outcomes; ᴯ Such as ≥18 years or ≥30 years; C Environmental Benefits Mapping and Analysis Program using the concentration response function from chronic bronchitis [63], acute bronchitis [64], all-cause mortality [65,104], COPD hospitalization (Moolgavgkar 2000a, 2003) [66], asthma emergency room visits [67], work loss days [68], asthma (symptoms) [69], minor-restricted activity days [70], acute MI [71], respiratory disease [72], lower respiratory symptoms [73], and cough among asthmatic children [74]; D Probable, but not specified explicitly in the text; ᴱ Health And Air Pollution Study in New Zealand to estimate the morbidity and mortality health costs associated with traffic emissions [82]; F CVD admission >64 years: [75]; ᴳ Mortality: <75 and >75 years, respiratory disease (65 years) [76], and lung cancer [104] Morbidity: CVD, respiratory disease [76], and lung cancer [104]; H Method of transport emission estimation is quite vague in determination of emission factors; I External cost of energy to estimate the automotive pollution impact on health in Europe [81]; J Cerebrovascular disease and lower respiratory tract infection [77], preterm weight [78], low term weight [79], and CVD (Mustafic 2012) [80]; K Value of a Life Year: calculation of monetary benefits of mortality reduction using a life tables approach. …”
Section: Resultsmentioning
confidence: 99%
“…

PM2.5: Particulate matter less than 2.5 µm; PM10: particulate matter less than 10 µm; BS: black soot; CP: cardiopulmonary; RM: respiratory mortality. ᴬ Age groups according to health outcomes; ᴯ Such as ≥18 years or ≥30 years; C Probable, but not specified explicitly in the text; D External cost of energy to estimate the automotive pollution impact on health in Europe [81]; E Calculation based on the actual number of participants who changed mode from car to bicycle; F Estimated for hypothetical individuals who changed transport mode from car to bicycle; G Cerebrovascular disease and lower respiratory tract infection [77], preterm weight [78], low term weight [79], and CVD (Mustafic 2012) [80]; H Value of a Life Year: calculation of monetary benefits of mortality reduction using a life tables approach.

…”
Section: Resultsmentioning
confidence: 99%
“…Qian et al (2008) found a synergistic effect of PM 10 and high temperatures on daily cardio-respiratory (Bell et al, 2007;Confalonieri et al, 2007;Dominici et al, 2006;Fiala et al, 2003;IPCC, 2007a;Katsouyanni et al, 1993;Knowlton et al, 2004;Koken et al, 2003;Mauzerall et al, 2005;Ordonez et al, 2005;Rainham and Smoyer-Tomic, 2003;Ren and Tong, 2006) ▪ The elderly and individuals with pre-existing cardio-respiratory disease may be more vulnerable to these effects Altered exposure and risk ▪ Some populations may experience increases or decreases in POP exposures and health risks depending on the region and diet of exposed individuals (Bard, 1999;Gordon, 1997;McKone et al, 1996;Watkinson et al, 2003) ▪ Pesticides may impair mechanisms of temperature regulation especially during times of thermal stress Increased susceptibility to pathogens ▪ Toxicants can suppress immune function, and climate-induced shifts in disease vector range will result in novel pathogen exposure (Abadin et al, 2007;Haines et al, 2006;Lipp et al, 2002;Nagayama et al, 2007;Patz et al, 2005;Rogers and Randolph, 2000;Smialowicz et al, 2001) ▪ Immune system impairment linked to toxicants may increase human vulnerability to climate shifts in pathogens ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible exposures may sensitize individuals to allergic disease ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible mortality in Wuhan, China. The PM 10 effects were strongest on extremely high temperature days (daily average temperature 33.1°C) and weakest during normal temperature days (daily average temperature 18°C).…”
Section: Air Pollutants and Cardio-respiratory Diseasementioning
confidence: 98%
“…However, a number of studies suggest that the toxicity of ozone and PM will be exacerbated with global warming, and some of these data support that older adults will be especially vulnerable (Bell et al, 2007;Confalonieri et al, 2007;Dominici et al, 2006;Fiala et al, 2003;IPCC, 2007c;Katsouyanni et al, 1993;Knowlton et al, 2004;Koken et al, 2003;Mauzerall et al, 2005;Ordonez et al, 2005;Rainham and Smoyer-Tomic, 2003;Ren and Tong, 2006). Other potential interactions between climate change and toxicant exposure include increased susceptibility to pathogens (Abadin et al, 2007;Nagayama et al, 2007;Smialowicz et al, 2001) and aeroallergens (D'Amato et al, 2002;Diaz-Sanchez et al, 2003;Epstein, 2005;Janssen et al, 2003).…”
Section: Effects Of Climate Change On Contaminant-linked Human Healthmentioning
confidence: 99%
See 1 more Smart Citation